(untitled) (Bangladesh Journal of Neuroscience, 2026)
Neuromyelitis optica spectrum disorders (NMOSD) previously known as Devic disease or Neuromyelitis optica (NMO) are inflammatory disorders of the central nervous system characterized by severe immune-mediated demyelination and axonal damage predominantly targeting optic nerves and spinal cord. Long segment myelitis, severe optic neuritis, and/or bouts of intractable vomiting and hiccups are classic presentations of the disease and may alert the clinician to the diagnosis. Approximately 75% of patients have antibodies against aquaporin-4. Previously, to diagnose NMO, optic nerve involvement was mandatory but in recent times concept of NMO has changed to NMOSD where we can categorize NMOSD even without optic nerve involvement. In this study we have discussed about a 22 years old lady presented to our inpatient department with inability to walk & incontinence of bowel & bladder. MRI spine showed long segment myelitis involving C5 to D6 level & CSF study revealed Aquaporin-4 (AQP4) Ab positive but optic nerves were normal. We diagnosed her as a case of NMOSD. She was put on intravenous methyl prednisolone 1 g daily for 5 days, followed by oral prednisolone and her muscle power improved to a extent that she could walk with assistance. Thereafter she was given azathioprine with good compliance.